2020
DOI: 10.1149/1945-7111/ab6160
|View full text |Cite
|
Sign up to set email alerts
|

Review—Zn–Mn Electrodeposition: A Literature Review

Abstract: To improve zinc coating performances in harsh environments, alloying Zn with other metals is an alternative way to generate advanced alloys with better corrosion properties. Zn binary alloys are extensively used in automotive industry for sacrificial corrosion protection of steel. Among Zn alloys, it has been reported that Zn-Mn coatings confer the highest anticorrosive properties, particularly those containing 10%-30% Mn. Zn-Mn alloys can be obtained by electrodeposition, a straightforward and low cost techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 80 publications
(464 reference statements)
0
11
0
Order By: Relevance
“…As not expected, the Mn content into the alloy deposited under 40 mA/cm 2 slightly arises from 0.3 to 0.98%. Accordingly, a highly concentrated bath on Mn 2+ ions is not recommended from a practical view due to the high cost of manganese salts [18] S e p a r a t e l y , S D I P N S c o n t a i n i n g a b o u t 9 2 % diisopropylnaphthalene sulfonate was added to the base solution S Zn-Mn . SDIPNS is able to perform a dual function in formulations by providing both surfactant and hydrotrope properties.…”
Section: Preparation Of Specimens and Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…As not expected, the Mn content into the alloy deposited under 40 mA/cm 2 slightly arises from 0.3 to 0.98%. Accordingly, a highly concentrated bath on Mn 2+ ions is not recommended from a practical view due to the high cost of manganese salts [18] S e p a r a t e l y , S D I P N S c o n t a i n i n g a b o u t 9 2 % diisopropylnaphthalene sulfonate was added to the base solution S Zn-Mn . SDIPNS is able to perform a dual function in formulations by providing both surfactant and hydrotrope properties.…”
Section: Preparation Of Specimens and Electrolytesmentioning
confidence: 99%
“…Ammonium ions are also used as efficient complexing agent. Such complexing agents bring the deposition potential of Zn closer to that of Mn due to the high relative formation constant of the complex formed with Zn 2+ ions [18,29,30]. Meanwhile, they pose an environmental problem in view that ammonia hinders or completely inhibits metal hydroxide precipitation during the treatment of the related wastewater by the widespread neutralization/precipitation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Among these alloys, Zn-Mn was reported to provide the most promising anticorrosive properties. [3][4][5] This is first due to the lower electrochemical potential of Mn compared to that of Zn, resulting in an increase in the cathodic protection over pure Zn. [4,6,7] Second, Mn was reported to dissolve preferentially into Mn 2+ ions during the corrosion of Zn-Mn alloys.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Among the means to obtain Zn-Mn anticorrosive coatings, pulse electroplating is attractive since this approach allows to obtain homogeneous, compact, and high Mn content deposits. [5,[16][17][18][19] Moreover, no additives are required in the bath, preventing the presence of impurities in the layers. While the electrodeposition of Zn-Mn coatings was largely reported in the literature, the vast majority of the research was focused on the material and anticorrosive properties of the deposits at the laboratory scale.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc-manganese alloy coatings are anodic coatings, for which the free potential is more negative than that of the part to be protected (steel). Several studies have reported that, in an aggressive environment where sodium chloride and sulfur dioxide are present [4,5], the zinc-manganese alloy coating may show good corrosion resistance [6][7][8]. According to the literature, several properties, namely, composition, morphology, and structural properties, of deposits strongly affect their corrosion behavior.…”
Section: Introductionmentioning
confidence: 99%